Formation of micro/nano pits with high catalytic activity on Fe80B20 amorphous alloy. (15th August 2018) - Zhang, X.H.; Zeng, Y.Q.; Yin, L.; Jiang, J.Q.; Pan, Y.; Li, R.; Liu, L.; Li, T.; Chan, K.C.
Highlights: Highly porous surface was prepared by forming pits on the Fe80 B20 amorphous alloy. Pit size on Fe-based amorphous alloys can be tuned by the etching potential. Micro/nano pits improve azo-dye degradation efficiency of Fe80 B20 amorphous alloy. Abstract: In this work, micro/nano size pits were introduced to the surface of Fe80 B20 amorphous ribbons by electrochemical etching treatment. The results show that the size of the pits is more sensitive to the applied etching potential, while the pit homogeneity is time dependent. The etching treatment at −0.30 V ( vs saturated calomel electrode) for three hours in 1 M HCl solution saturated by KCl leads to the formation of numerous pits with an average diameter of 222 nm. The large amount of pits results in higher degradation efficiency on Direct Blue 15 when compared with the as-spun amorphous alloy.